Effects of Violence Against Women in Suqûth al-Imâm by Nawal el-Sa’dâwi: A Radical Feminism Study - Syarifuddin Syarifuddin (UIN Sunan Kalijaga Yogyakarta, 2020)
This study aims to describe the forms and effects of violence experienced by the main female character in Suqûth Al-Imâm by Nawal El-Sa’dawi. As a woman, el-Sa’dâwi has a high sensitivity in describing the feelings of a woman experiencing violence. The method used to uncover the forms and effects of violence on women in this novel is descriptive qualitative. The data displayed are words, phrases, sentences, and discourses that contain elements of violence against women. Applying the style of radical feminism in analyzing the data, this research shows that, first, the forms of violence against the main character are physical, psychological and sexual violence; second, the effects of violence experienced by the main character are physical injury, psychological disorders, and behavioral disorders. Thus, it concludes that repeated violence against women may result in prolonged suffering and is not acceptable to women both physically and mentally.